Comparison of blood flow restriction devices and their effect on quadriceps muscle activation. (May 2021) - Bordessa, Jacqueline M.; Hearn, Mason C.; Reinfeldt, Alexander E.; Smith, Tyler A.; Baweja, Harsimran S.; Levy, Susan S.; Rosenthal, Michael D.
Abstract: Objectives: Blood flow restriction training (BFRT) provides an alternative approach to traditional strength training. The purpose of this study was to determine differences in quadriceps muscle activation, subject reported pain, and perceived exertion between three exercise conditions: low-load resistance BFRT with (1) regulated and (2) standardized devices, and (3) high-load resistance exercise without BFRT. Design: Randomized cross over study. Setting: XX University Biomechanics laboratory. Participants: Thirty-four healthy subjects (18 male/16 female) each completed three randomized sessions of knee extensions using Delfi's Personalized Tourniquet System (R) at 30% of 1 repetition maximum (1RM), the B-Strong™ device (S) at 30% 1RM, and high-load resistance exercise (HL) at 80% 1RM. Main outcome measures: Quadriceps EMG activity, numeric pain rating scale (NPRS), and perceived exertion (OMNI-RES) were recorded. Results: Average and peak EMG were greater in HL sessions than both S and R (p < .001). NPRS was greater in the R sessions compared to both S (p < .001) and HL (p < .001). OMNI-RES was greater in the R sessions compared to S (p < .02) and HL (p < .001). No differences (p > .05) in average or peak EMG activation were found between S and R sessions. Conclusions: Quadriceps EMG amplitude was greater during high-load resistance exercise versus low-load BFR exercise and there were no differences in EMG findings between BFRT devices. Highlights: Low load BFRT produced lower EMG activity in comparison to high-load resistance exercise. Utilization of BFRT was better tolerated using a "standard" BFR device. With a "regulated" BFR device, starting with an occlusion pressure below 80% of LOP may improve tolerance. Men and women had similar quadriceps activity and perceptual responses to the respective exercise conditions.